The grey wolf ebook - Penny, Louise (Chief Inspector Armand Gamache, 2024)
INSTANT #1 NEW YORK TIMES BESTSELLER The 19th mystery in the #1 New York Times -bestselling Armand Gamache series. Relentless phone calls interrupt the peace of a warm August morning in Three Pines. Though the tiny Québec village is impossible to find on any map, someone has managed to track down Armand Gamache, head of homicide at the Sûreté, as he sits with his wife in their back garden. Reine-Marie watches with increasing unease as her husband refuses to pick up, though he clearly knows who is on the other end. When he finally answers, his rage shatters the calm of their quiet Sunday morning. That's only the first in a sequence of strange events that begin THE GREY WOLF, the nineteenth novel in Louise Penny's #1 New York Times -bestselling series. A missing coat, an intruder alarm, a note for Gamache reading "this might interest you", a puzzling scrap of paper with a mysterious list—and then a murder. All propel Chief Inspector Gamache and his team toward a terrible realization. Something much more sinister than any one murder or any one case is fast approaching. Armand Gamache, Jean-Guy Beauvoir, his son-in-law and second in command, and Inspector Isabelle Lacoste can only trust each other, as old friends begin to act like enemies, and long-time enemies appear to be friends. Determined to track down the threat before it becomes a reality, their pursuit takes them across Québec and across borders. Their hunt grows increasingly desperate, even frantic, as the enormity of the creature they're chasing becomes clear. If they fail the devastating consequences would reach into the largest of cities and the smallest of villages. Including Three Pines.